Financial Distress Prediction Study in Retail Companies : Case Study on Financial Statements on the Indonesia Stock Exchange for the 2017-2021 Period - Asmadhini Handayani Rahmah Rahmah; Yusaniah (Politeknik Caltex Riau, 2022)
The rapid development of payment digitalization and the Covid-19 outbreak that is now hitting has brought changes in consumer interest in shopping using online services, this is due to the convenience and convenience obtained during online shopping, this change has an impact on companies that only provide offline services to sell their products, especially in the financial condition of the company which is feared to experience financial distress. Financial distress is a condition of the company's financial decline accompanied by the company's inability to pay the debts that have matured. This study aims to determine and analyze the risk of financial distress in the company under study.The data used is secondary data in the form of financial statements of PT Matahari Putra Prima Tbk, PT Matahari Department Store Tbk and PT Ramayana Lestari Sentosa Tbk in the 2017-2021 period, which will be processed using three models of financial distress prediction analysis, namely the zmijewski model, the altman model and the springate model. The results obtained can later be used as an early warning system to find out the condition of the company under study and also materials for making decisions for investors and creditors.